GAMBARAN KLINIS DAN ELEKTRONEUROGRAFI SINDROMA TEROWONGAN KARPALl PADA PENYANDANG DM TIPE 2 PASCATERAPI STEROID INTRAKANAL - Ferdhi Adha*, Bob Santoso Wibowo**, Manfaluthy Hakim**, Herqutanto*** (NEURONA, 2009)
BACKGROUND CARPAL TUNNEL SYNDROME OCCURRS VERY OFTEN AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS HOWEVER THERAPIES FOR CTS THESE PATIENTS ARE LIMITED BESIDE SURGERY THE ONLY ALTERNATIVE THERAPY AVAILABLE FOR THIS CONDITION IS INTRACANAL STEROID THERAPY OBJECTIVE OF THE RESEARCH IS TO ASSESS THE CLINICAL PROFILE AND ELECTRONEUROGRAPHY OF CTS IN TYPE 2 DIABETIC PATIENTS BEFORE AND AFTER THERAPY WITH INTRACANAL STEROID